Deciphering the Evolution of Cephalosporin Resistance to Ceftolozane-Tazobactam in Pseudomonas aeruginosa - Melissa D. Barnes (American Society for Microbiology, 2018)
ABSTRACT Pseudomonas aeruginosa produces a class C β-lactamase (e.g., PDC-3) that robustly hydrolyzes early generation cephalosporins often at the diffusion limit; therefore, bacteria possessing these β-lactamases are resistant to many β-lactam antibiotics. In response to this significant clinical threat, ceftolozane, a 3′ aminopyrazolium cephalosporin, was developed. Combined with tazobactam, ceftolozane promised to be effective against multidrug-resistant P. aeruginosa. Alarmingly, Ω-loop variants of the PDC β-lactamase (V213A, G216R, E221K, E221G, and Y223H) were identified in ceftolozane/tazobactam-resistant P. aeruginosa clinical isolates. Herein, we demonstrate that the Escherichia coli strain expressing the E221K variant of PDC-3 had the highest minimum inhibitory concentrations (MICs) against a panel of β-lactam antibiotics, including ceftolozane and ceftazidime, a cephalosporin that differs in structure largely in the R2 side chain. The kcat values of the E221K variant for both substrates were equivalent, whereas the Km for ceftolozane (341 ± 64 µM) was higher than that for ceftazidime (174 ± 20 µM). Timed mass spectrometry, thermal stability, and equilibrium unfolding studies revealed key mechanistic insights. Enhanced sampling molecular dynamics simulations identified conformational changes in the E221K variant Ω-loop, where a hidden pocket adjacent to the catalytic site opens and stabilizes ceftolozane for efficient hydrolysis. Encouragingly, the diazabicyclooctane β-lactamase inhibitor avibactam restored susceptibility to ceftolozane and ceftazidime in cells producing the E221K variant. In addition, a boronic acid transition state inhibitor, LP-06, lowered the ceftolozane and ceftazidime MICs by 8-fold for the E221K-expressing strain. Understanding these structural changes in evolutionarily selected variants is critical toward designing effective β-lactam/β-lactamase inhibitor therapies for P. aeruginosa infections. IMPORTANCE The presence of β-lactamases (e.g., PDC-3) that have naturally evolved and acquired the ability to break down β-lactam antibiotics (e.g., ceftazidime and ceftolozane) leads to highly resistant and potentially lethal Pseudomonas aeruginosa infections. We show that wild-type PDC-3 β-lactamase forms an acyl enzyme complex with ceftazidime, but it cannot accommodate the structurally similar ceftolozane that has a longer R2 side chain with increased basicity. A single amino acid substitution from a glutamate to a lysine at position 221 in PDC-3 (E221K) causes the tyrosine residue at 223 to adopt a new position poised for efficient hydrolysis of both cephalosporins. The importance of the mechanism of action of the E221K variant, in particular, is underscored by its evolutionary recurrences in multiple bacterial species. Understanding the biochemical and molecular basis for resistance is key to designing effective therapies and developing new β-lactam/β-lactamase inhibitor combinations.